Hybrid Simulation Framework: Advanced and Secure Training - Santos, Lucas S. dos; Maria, Luiz C. G.; M. Junior, Erisvaldo F.; Machado, Raphael C. S. (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2024: Anais do LI Seminário Integrado de Software e Hardware, 2024)
Simulation has been employed as a teaching, training, and procedure validation tool in several fields, such as medicine, education, and the military. Although the use of Simulation presents advantages compared to traditional methodologies, several challenges exist in designing, developing, and implementing these simulation systems. These challenges become even more complex when the project involves the development of hybrid simulators. These simulators integrate physical and virtual systems. This integration makes these simulators more immersive, enhancing the simulation experience. The present work describes a framework for developing hybrid simulator systems. The framework was applied in the “Tupi” Class Submarines retrofit simulator project. The results show that the framework is a feasible solution for hybrid simulation systems, validated through collaboration with the Brazilian Navy’s technical team (CIAMA).